The importance of storytelling in shaping attitudes towards jaguars (Panthera onca) and parallels with folklore of non-indigenous traditional communities of the Central Amazon Basin - Charters, Jacob Daniel (2019)
Large carnivores often elicit strong human emotions. Given that most people will never have a significant encounter with wild carnivores implies that these attitudes are based on indirect influences such as media, education, social norms, and peer-peer interactions. Understanding the mechanisms of how people form attitudes towards carnivores is important for deciding mitigation strategies aimed at changing attitudes. In Brazil, most human-carnivore conflict research to date has investigated perceptions towards jaguars (Panthera onca) in association with the depredation of livestock. Where livestock absent, or of low economic importance, such as in many areas of the Amazon Basin, the rate of hunting of jaguars remains high, yet the reason for negative attitudes and acceptance of killing jaguars in these areas remains unclear. This study, conducted in the town of Beruri and adjacent four riverine communities along the lower Purus River, in the Brazilian state of Amazonas, uses semi-structured questionnaires and qualitative analysis to assess how social norms and peer-peer interactions- in the form of storytelling- influence attitudes towards jaguars. Parallels are made between how accounts of encounters with jaguars (and other wildlife) and regional folklore permeate the communities and are accepted by residents. Finally, the influence of demographic factors are assessed. Results show negative correlations between attitude and the level of belief in folklore. This trend was similar across age, sex, community, and relationship the surrounding habitat. Understanding the importance of storytelling and the verbal transmission of ideas between peers in non-indigenous traditional communities is essential for changing attitudes towards wildlife for conservation purposes. This study highlights that attitudes are often robust, and not based on factual information. Thus, any attitude mitigation projects should look past the traditional environmental education models, and use a multifaceted approach for changing attitudes towards carnivores.